Characterization of Antibodies for Grain‐Specific Gluten Detection. Issue 3 (15th February 2016) - Sharma, Girdhari M.; Rallabhandi, Prasad; Williams, Kristina M.; Pahlavan, Autusa
Abstract: Gluten ingestion causes immunoglobulin E (IgE)‐mediated allergy or celiac disease in sensitive individuals, and a strict gluten‐free diet greatly limits food choices. Immunoassays such as enzyme‐linked immunosorbent assay (ELISA) are used to quantify gluten to ensure labeling compliance of gluten‐free foods. Anti‐gluten antibodies may not exhibit equal affinity to gluten from wheat, rye, and barley. Moreover, because wheat gluten is commonly used as a calibrator in ELISA, accurate gluten quantitation from rye and barley contaminated foods may be compromised. Immunoassays utilizing grain‐specific antibodies and calibrators may help improve gluten quantitation. In this study, polyclonal antibodies raised against gluten‐containing grain‐specific peptides were characterized for their immunoreactivity to gluten from different grain sources. Strong immunoreactivity to multiple gluten polypeptides from wheat, rye, and barley was observed in the range 34 to 43 kDa with anti‐gliadin, 11 to 15 and 72 to 95 kDa with anti‐secalin, and 30 to 43 kDa with anti‐hordein peptide antibodies, respectively. Minimal or no cross‐reactivity with gluten from other grains was observed among these antibodies. The anti‐consensus peptide antibody raised against a repetitive amino acid sequence of proline and glutamine exhibited immunoreactivity to gluten from wheat, rye, barley, and oat. The antibodies exhibited similar immunoreactivity with most of the corresponding grain cultivars by ELISA. The high specificity and minimal cross‐reactivity of grain‐specific antibodies suggest their potential use in immunoassays for accurate gluten quantitation.